A model approach to include wood properties in log sorting and transportation planning. Issue 3 (2nd July 2016) - Andersson, Gert; Flisberg, Patrik; Nordström, Maria; Rönnqvist, Mikael; Wilhelmsson, Lars
ABSTRACT: There is a trend that sawmills are more focused on particular valuable products in their production. This has led to an increased demand for sawlogs that are better adapted to the target products and production efficiency. Depending on the product being produced there are different log properties which are better adapted for certain products than others. Sawmills can require hard constraints on log properties such as length, diameter, internode length and sound knots. Some properties are not required but are desired as they make the production more efficient or increase the frequencies of preferred products. In these cases, we include an added value corresponding to what the industry is willing to pay for improved adaptation of the raw material. To achieve this, we propose an optimization model that integrates logging operations (bucking and forwarding) at harvest areas, transportation planning and flexible description of demand at sawmills. High flexibility for sorting at harvest areas may require additional piles of different properties to be generated. Instead of using a large number of special assortments, we allow many sorting alternatives depending on the requirements used at the industries. The transportation planning decides on the flows between harvest areas and sawmills while considering demand and supply. Even if many potential piles are used in the planning model, only a few may be used in practice. We present computational results based on 16 synthesized geographically distributed harvest areas, each representing all regional variation of mature sample trees from the Swedish National Forest Inventory and a number of sawmills.